Efficacy and tolerability of toremifene and tamoxifen therapy in premenopausal patients with operable breast cancer: a retrospective analysis - Qin, T. (Multimed Inc., 2013)
BACKGROUND: Given the use of tamoxifen as standard treatment for hormone receptor–positive breast cancer, the use of toremifene as an adjuvant endocrine therapy has not been widely examined. The present retrospective study compared the efficacy and safety of toremifene and tamoxifen in the treatment of operable hormone receptor–positive breast cancer in premenopausal women. METHODS: Premenopausal patients with hormone receptor– positive operable breast cancer were eligible. Enrolled patients (n = 1847) received either 60 mg toremifene (n = 396) or 20 mg tamoxifen (n = 1451) daily for a minimum of 5 years after surgery. Disease-free survival (dfs) was the primary endpoint. Overall survival (os) and time to distant recurrence were secondary endpoints. RESULTS: Treatment with toremifene and tamoxifen resulted in no between-group differences in dfs (p = 0.659) or os (p = 0.364). Mean dfs was 10.3 years for both groups. Mean os was 11.2 years for the toremifene group and 11.1 years for tamoxifen group. The 5-year dfs rate was 87.0% in the toremifene group and 85.0% in the tamoxifen group. The 5-year survival rate was 94.3% in the toremifene group and 93.5% in the tamoxifen group. Adverse events rates were similar in the two groups, with the exception of irregular menses, which occurred at a higher rate in the tamoxifen group than in the toremifene group (10.0% vs. 6.3%, p = 0.025). CONCLUSIONS: In this retrospective study, the efficacy and safety profiles of toremifene and tamoxifen for the treatment of operable hormone receptor–positive breast cancer in premenopausal women were similar.